Bariatric Surgery in the Management of Morbid Obesity in Individuals with HIV Infection: A Scoping Review - Alamri, Abdulrahman Manaa; Iannelli, Antonio; Alasmari, Mansour Yousef; AlWadai, Hajar Hassan Ali; Alromayan, Mohammed; Alsareii, Saeed Ali; Chierici, Andrea (International Journal of Innovative Research in Medical Science, 2023)
The escalating incidence of obesity in HIV patients undergoing antiretroviral therapy (ART) is a significant health concern. This scoping review investigates the impact of bariatric surgery on HIV patients suffering from severe obesity. Following PRISMA-ScR guidelines, we meticulously searched PubMed and Scopus databases and selected 11 studies published in English from various countries. These studies provided quantitative evidence of weight loss or remission of severe obesity in HIV patients post-bariatric surgery. We used the JBI checklists for quality assessment relevant to observational study designs. The results from the 11 selected studies, primarily case series conducted in different geographical locations, showed significant reductions in Body Mass Index (BMI) and percentage of excess weight loss (%EWL) following Sleeve Gastrectomy (SG), Roux-en-Y Gastric Bypass (RYGB), and combined bariatric surgery procedures. This review highlights the potential of SG and RYGB in achieving significant weight loss in HIV patients. However, it also emphasises the need for careful interpretation due to variations in study designs and quality. It underscores the need for future research employing rigorous methodologies to strengthen the evidence base at this complex intersection of HIV, obesity, and bariatric surgery.